Halogen-free flame-retardant o-cresol formaldehyde type high-molecular-weight epoxy resin solution for copper-clad plate as well as preparation method and application thereof

By using halogen-free flame-retardant high molecular weight epoxy resin solution prepared from ortho-cresol epoxy resin and other materials in the copper clad industry, the problems of plate flow glue loss and poor humidity and heat resistance are solved, and high heat resistance and low heat resistance are achieved The resin with water absorption and high toughness meets the application needs of copper clad plates and improves flame retardant performance through the composition.

CN119161561AInactive Publication Date: 2024-12-20JIANGSU EMT NEW MATERIAL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411667829.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing halogen-free flame-retardant epoxy resins are used in the copper clad industry with large losses in the pressure plate flow glue, poor moisture and heat resistance, and large brittleness, which limits their application in copper clad plates.

Method used

Using o-cresol epoxy resin, 9,10-dihydro-9-oxa-10-phosphophenol-10-oxide, bisphenol F, ethyltriphenylphosphine acetate and tetraethylammonium chloride Halogen-free flame-retardant high molecular weight epoxy resin solution prepared by catalytic reaction is diluted by cyclohexanone to form a resin with high heat resistance and low water absorption, and is combined with linear phenolic resin, ODA-type benzoxazine resin and butanone In combination, a resin for copper clad plate with high toughness and low flow rate was prepared.

Benefits of technology

It improves the heat resistance, toughness and water absorption rate of the resin, reduces the loss rate of the flow glue, meets the performance requirements of copper clad plates when drilling, and realizes the flame retardancy of UL94-V0.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 06VLVDR5IG2RVPQK6TTFORQWXYTIRJT8QE1EAPH2
    Figure 06VLVDR5IG2RVPQK6TTFORQWXYTIRJT8QE1EAPH2
  • Figure JXDF08GH8RMPPZWJ5GNRJNEG4TTEHWC5SDZKQD5F
    Figure JXDF08GH8RMPPZWJ5GNRJNEG4TTEHWC5SDZKQD5F
  • Figure VUVY3FFIA0XGAMLWOIAQXUCY7SJTYXAXIZNGIXBA
    Figure VUVY3FFIA0XGAMLWOIAQXUCY7SJTYXAXIZNGIXBA
Patent Text Reader

Abstract

The invention relates to a halogen-free flame-retardant o-cresol formaldehyde type high-molecular-weight epoxy resin solution for a copper-clad plate as well as a preparation method and application thereof. The preparation method comprises the following steps: adding cyclohexanone into a reaction kettle, starting stirring and heating, adding o-cresol formaldehyde epoxy resin, and uniformly dissolving the o-cresol formaldehyde epoxy resin; adding DOPO into the reaction kettle, then adding ethyl triphenyl phosphine acetate, and heating for reaction; then adding bisphenol F and tetraethylammonium chloride into the reaction kettle for reaction; after the reaction is finished, cyclohexanone is dropwise added, and the mixture is gradually cooled and stirred to prepare the halogen-free flame-retardant o-cresol formaldehyde type high-molecular-weight epoxy resin solution for the copper-clad plate. The halogen-free flame-retardant epoxy resin has the advantages that the o-cresol formaldehyde epoxy resin with high heat resistance and low water absorption and the DOPO are adopted to generate the halogen-free flame-retardant epoxy resin with high heat resistance and low water absorption under the action of the catalyst, and meanwhile, bisphenol F further reacts with an epoxy group, so that the toughness of the resin is improved, the requirement that a copper-clad plate does not crack and fall powder when drilling is applied is met, and the service life of the copper-clad plate is prolonged. And the resin is not easy to flow and lose during plate pressing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of synthesis modification and application of organic compound epoxy resin, in particular to a halogen-free flame retardant o-cresol type high molecular weight epoxy resin solution for copper clad laminates, a preparation method of the halogen-free flame retardant o-cresol type high molecular weight epoxy resin solution for copper clad laminates, and a halogen-free flame retardant o-cresol type high molecular weight epoxy resin solution composition for copper clad laminates. Background Art

[0002] Copper clad laminate is the foundation of the electronics industry. It is mainly used for processing and manufacturing printed circuit boards (PCBs), and is widely used in various electronic products such as computers, new energy vehicles, mobile communications, and home appliances. Existing resins for copper clad laminates are basically produced by various common bisphenol A epoxy resins, brominated epoxy resins, halogen-free flame-retardant epoxy resins, phenolic epoxy resins, benzoxazine resins, bismaleimide resins, etc., with curing agents and a large amount of solvents. However, when the current common halogen-free flame-retardant epoxy resins are used in the copper clad laminate industry, the pressure plate has a large glue flow loss (>2%), the board has poor moisture and heat resistance (Tg <140℃ is low, water absorption rate >0.6% is high), and it is brittle (impact strength <10KJ / m2), which limits its application in copper clad laminates. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a halogen-free flame retardant o-cresol type high molecular weight epoxy resin solution for copper clad laminates and a preparation method thereof, as well as a halogen-free flame retardant o-cresol type high molecular weight epoxy resin solution composition for copper clad laminates, which can solve the problems in the prior art that when halogen-free flame retardant epoxy resins are used in the copper clad laminate industry, the pressure plate has large glue flow loss, the plate has poor moisture and heat resistance, and is relatively brittle, which limits its application in copper clad laminates.

[0004] In order to solve the above technical problems, the technical solution of the present invention is: a halogen-free flame-retardant o-cresol type high molecular weight epoxy resin solution for copper clad laminates, characterized in that: the halogen-free flame-retardant o-cresol type high molecular weight epoxy resin solution is prepared by catalytic reaction of o-cresol type epoxy resin, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), bisphenol F, ethyl triphenylphosphine acetate, and tetraethylammonium chloride, and then diluted by cyclohexanone, and the halogen-free flame-retardant o-cresol type high molecular weight epoxy resin has a chemical structure formula as shown below: .

[0005] Furthermore, the mass percentage of solid content in the halogen-free flame-retardant o-cresol-formaldehyde high molecular weight epoxy resin solution for copper-clad laminates is 60±2%, the viscosity thereof is 1000-2000 mpas, and the number average molecular weight is 3000-5000.

[0006] Furthermore, the o-cresol-formaldehyde epoxy resin has a chemical structural formula as shown below: , where n=3-7.

[0007] A method for preparing a halogen-free flame-retardant o-cresol-formaldehyde type high molecular weight epoxy resin solution for copper clad laminates comprises the following steps: S1: Add 30 parts by mass of cyclohexanone into a reaction kettle, start stirring, raise the temperature to 130° C., and slowly add 90 to 110 parts by mass of o-cresol epoxy resin to make it dissolve evenly; S2: Add 20-30 parts by weight of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide flame retardant monomer to the reactor, and then add 0.1-0.5 parts by weight of ethyl triphenylphosphine acetate, stir, slowly heat up to 130° C., accelerate the exothermic reaction, use cooling water to cool, control the temperature at 160-170° C., and react for 3-5 hours; S3: Then, 10 to 15 parts by weight of bisphenol F and 0.01 to 0.05 parts by weight of tetraethylammonium chloride are added to the reaction kettle, and the temperature is controlled to 170 to 180° C. to react for 4 to 6 hours; S4: After the reaction is completed, 50 to 75 parts by weight of cyclohexanone is slowly added dropwise, the temperature is gradually lowered, and finally stirred at 60° C. for 2 hours to obtain a halogen-free flame-retardant o-cresol-formaldehyde high molecular weight epoxy resin solution for copper-clad laminates having a solid mass percentage of 60±2%.

[0008] A halogen-free flame-retardant o-cresol-formaldehyde type high molecular weight epoxy resin solution composition for copper-clad laminates comprises the following components: 90 to 110 parts by weight of a halogen-free flame-retardant o-cresol-formaldehyde type high molecular weight epoxy resin solution for copper-clad laminates having a solid content of 60±2%, 10 to 15 parts by weight of a linear phenolic resin, 10 to 12 parts by weight of an ODA type benzoxazine resin, 0.2 to 1 parts by weight of 2-ethyl-4-methylimidazole and 10 to 20 parts by weight of butanone.

[0009] Furthermore, the structural formula of the linear phenolic resin is: , where n=10-15.

[0010] Furthermore, the structural formula of the ODA-type benzoxazine resin is: .

[0011] Furthermore, the structural formula of the 2-ethyl-4-methylimidazole is: .

[0012] The invention has the advantages that: the o-cresol epoxy resin with high heat resistance and low water absorption rate and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide are used to generate the halogen-free flame-retardant epoxy resin with high heat resistance and low water absorption rate under the action of ethyl triphenylphosphine acetate as a catalyst; at the same time, bisphenol F further reacts with the epoxy group to extend the length of the epoxy main chain, reduce the cross-linking density, and improve the toughness of the resin, so as to meet the requirement that the copper clad laminate does not crack and powder when drilling is used; and, through the chain extension of bisphenol F, the molecular weight of the resin is expanded to 3000-5000, and the resin is not easy to flow and lose when pressing the plate; The resin cured product prepared by the product of the present invention has a Tg of ≥160°C, high heat resistance, and an impact strength of ≥40KJ / m 2 , good toughness, water absorption rate <0.3%, low water absorption rate, press plate glue loss rate <0.4%, low press plate glue loss rate, flame retardancy meets UL94-V0, the copper clad laminate has good toughness and does not crack or powder when drilling, and is a resin for copper clad laminates with excellent comprehensive performance. DETAILED DESCRIPTION

[0013] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with specific implementation methods. The following examples can enable technicians in this field to understand the present invention more comprehensively, but the present invention is not limited to the scope of the embodiments.

[0014] This specific implementation adopts the following technical scheme: the halogen-free flame-retardant o-cresol-formaldehyde type high molecular weight epoxy resin solution is prepared by catalytic reaction of o-cresol-formaldehyde epoxy resin, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), bisphenol F, ethyl triphenylphosphine acetate, and tetraethylammonium chloride, and then diluted with cyclohexanone. The halogen-free flame-retardant o-cresol-formaldehyde type high molecular weight epoxy resin has the following chemical structure formula: .

[0015] The method for preparing the above-mentioned halogen-free flame-retardant o-cresol-formaldehyde type high molecular weight epoxy resin solution for copper-clad laminates comprises the following steps: S1: 30 parts by weight of cyclohexanone is added to a reaction kettle, stirring is started, the temperature is raised to 130° C., and 90 to 110 parts by weight of o-cresol epoxy resin is slowly added to make it dissolve evenly. The o-cresol epoxy resin has the following chemical structure formula: , where n=3-7.

[0016] S2: Add 20-30 parts by weight of DOPO flame retardant monomer to the reactor, and then add 0.1-0.5 parts by weight of ethyl triphenylphosphine acetate, stir, slowly heat up to 130°C, accelerate the exothermic reaction, use cooling water to cool, control the temperature at 160-170°C and react for 3-5 hours. The DOPO flame retardant monomer has the following chemical structure formula: ; Ethyl triphenylphosphine acetate has the following chemical structural formula: .

[0017] S3: Then, 10 to 15 parts by weight of bisphenol F and 0.01 to 0.05 parts by weight of tetraethylammonium chloride are added to the reaction kettle, and the temperature is controlled at 170 to 180° C. to react for 4 to 6 hours. Bisphenol F has the following chemical structural formula: ; Tetraethylammonium chloride has the following chemical structural formula: .

[0018] S4: After the reaction is completed, 50 to 75 parts by weight of cyclohexanone is slowly added dropwise, the temperature is gradually lowered, and finally stirred at about 60°C for 2 hours to obtain a halogen-free flame-retardant o-cresol-formaldehyde high molecular weight epoxy resin solution for copper clad laminates with a solid mass percentage of 60±2%, a viscosity of 1000 to 2000 mpas, and a number average molecular weight of 3000-5000.

[0019] The following is further described in conjunction with a number of embodiments: Examples 1-1 to 1-8 use different dosages and process conditions to react to prepare halogen-free flame-retardant o-cresol-formaldehyde type high molecular weight epoxy resin solutions for copper clad laminates, as shown in Table 1 below: Table 1: Formula (unit: kg) and process conditions of halogen-free flame-retardant o-cresol-formaldehyde high molecular weight epoxy resin solution for copper clad laminates: .

[0020] Temperature A in Table 1 is the reaction temperature in step S2, reaction time T1 is the reaction time in step S2, temperature B is the reaction temperature in step S3, and reaction time T2 is the reaction time in step S3.

[0021] A halogen-free flame-retardant o-cresol-formaldehyde type high molecular weight epoxy resin solution composition for copper-clad laminates comprises the following components: 90 to 110 parts by weight of a halogen-free flame-retardant o-cresol-formaldehyde type high molecular weight epoxy resin solution for copper-clad laminates having a solid content of 60±2%, 10 to 15 parts by weight of a linear phenolic resin, 10 to 12 parts by weight of an ODA type benzoxazine resin, 0.2 to 1 parts by weight of 2-ethyl-4-methylimidazole and 10 to 20 parts by weight of butanone.

[0022] The structural formula of linear phenolic resin is: , where n=10-15.

[0023] The structural formula of ODA type benzoxazine resin is: .

[0024] The structural formula of 2-ethyl-4-methylimidazole is: .

[0025] The halogen-free flame retardant o-cresol-formaldehyde high molecular weight epoxy resin solution for copper clad laminates with a solid mass percentage of 60% is the halogen-free flame retardant o-cresol-formaldehyde high molecular weight epoxy resin solution for copper clad laminates with a solid mass percentage of 60% in the above Examples 1-1 to 1-8, and the specific preparation steps are the same, which will not be described in detail here.

[0026] Examples 2-1 to 2-8 use different amounts to prepare halogen-free flame-retardant o-cresol-formaldehyde type high molecular weight epoxy resin solution compositions for copper clad laminates, as shown in Table 2 below.

[0027] Table 2: Formula of halogen-free flame-retardant o-cresol-formaldehyde type high molecular weight epoxy resin solution composition for preparing copper clad laminate (unit: mass parts): .

[0028] The performance results of copper-clad laminates prepared from halogen-free flame-retardant o-cresol-formaldehyde high molecular weight epoxy resin solution compositions of Examples 2-1 to 2-8 are shown in Table 3: Table 3: Performance results of copper-clad laminates prepared from halogen-free flame-retardant o-cresol-formaldehyde high molecular weight epoxy resin solution compositions of Examples 2-1 to 2-8: .

[0029] Example 3: Add 30 parts by mass of cyclohexanone to the reactor, start stirring, raise the temperature to 130°C, slowly add 90 parts by mass of o-cresol epoxy resin to make it dissolve evenly, then add 20 parts by mass of DOPO flame retardant monomer to the reactor, add 0.2 parts by mass of ethyl triphenylphosphine acetate, stir, slowly raise the temperature to 130°C, the reaction exotherm is accelerated, cool with cooling water, control the temperature at 160°C and react for 5 hours, then add 10 parts by mass of bisphenol F and 0.01 parts by mass of tetraethylammonium chloride to the reactor, control the temperature at 170°C and react for 6 hours, after the reaction is completed, slowly add 50 parts by mass of cyclohexanone dropwise, gradually cool, and finally stir at about 60°C for 2h to obtain a halogen-free flame retardant o-cresol type high molecular weight epoxy resin solution for copper clad laminates with a solid mass percentage of 60±2%, the viscosity of which is 1600mpas, and it is a yellow-brown liquid.

[0030] Example 4: Add 30 parts by mass of cyclohexanone to the reactor, start stirring, raise the temperature to 130°C, slowly add 110 parts by mass of o-cresol epoxy resin to make it dissolve evenly, then add 28 parts by mass of DOPO flame retardant monomer to the reactor, add 0.4 parts by mass of ethyl triphenylphosphine acetate, stir, slowly raise the temperature to 130°C, the reaction exotherm is accelerated, use cooling water to cool, control the temperature to 170°C and react for 3 hours, then add 15 parts by mass of bisphenol F and 0.05 parts by mass of tetraethylammonium chloride to the reactor, control the temperature to 180°C and react for 4 hours, after the reaction is completed, slowly add 75 parts by mass of cyclohexanone dropwise, gradually cool down, and finally stir at about 60°C for 2h to obtain a halogen-free flame retardant o-cresol type high molecular weight epoxy resin solution for copper clad laminates with a solid mass percentage of 60±2%, the viscosity of which is 1800mpas, and it is a yellow-brown liquid.

[0031] Example 5: Add 30 parts by mass of cyclohexanone to the reactor, start stirring, raise the temperature to 130°C, slowly add 100 parts by mass of o-cresol epoxy resin to make it dissolve evenly, then add 25 parts by mass of DOPO flame retardant monomer to the reactor, add 0.25 parts by mass of ethyl triphenylphosphine acetate, stir, slowly raise the temperature to 130°C, the reaction exotherm is accelerated, cool with cooling water, control the temperature at 165°C and react for 4 hours, then add 13 parts by mass of bisphenol F and 0.03 parts by mass of tetraethylammonium chloride to the reactor, control the temperature at 175°C and react for 5 hours, after the reaction is completed, slowly add 63 parts by mass of cyclohexanone dropwise, gradually cool, and finally stir at about 60°C for 2h to obtain a halogen-free flame retardant o-cresol type high molecular weight epoxy resin solution for copper clad laminates with a solid mass percentage of 60±2%, the viscosity of which is 1300mpas, and it is a yellow-brown liquid.

[0032] Example 6: Add 30 parts by mass of cyclohexanone to the reactor, start stirring, raise the temperature to 130°C, slowly add 96 parts by mass of o-cresol epoxy resin to make it dissolve evenly, then add 23 parts by mass of DOPO flame retardant monomer to the reactor, add 0.2 parts by mass of ethyl triphenylphosphine acetate, stir, slowly raise the temperature to 130°C, the reaction exotherm is accelerated, cool with cooling water, control the temperature at 163°C and react for 4.5 hours, then add 12 parts by mass of bisphenol F and 0.03 parts by mass of tetraethylammonium chloride to the reactor, control the temperature at 176°C and react for 4.5 hours, after the reaction is completed, slowly add 57 parts by mass of cyclohexanone dropwise, gradually cool, and finally stir at about 60°C for 2h to obtain a halogen-free flame retardant o-cresol type high molecular weight epoxy resin solution for copper clad laminates with a solid mass percentage of 60±2%, the viscosity of which is 1700mpas, and it is a yellow-brown liquid.

[0033] Example 7: Add 30 parts by mass of cyclohexanone to the reactor, start stirring, raise the temperature to 130°C, slowly add 105 parts by mass of o-cresol epoxy resin to make it dissolve evenly, then add 28 parts by mass of DOPO flame retardant monomer to the reactor, add 0.4 parts by mass of ethyl triphenylphosphine acetate, stir, slowly raise the temperature to 130°C, the reaction exotherm is accelerated, use cooling water to cool, control the temperature at 167°C and react for 3.5 hours, then add 13 parts by mass of bisphenol F and 0.04 parts by mass of tetraethylammonium chloride to the reactor, control the temperature at 174°C and react for 4.5 hours, after the reaction is completed, slowly add 68 parts by mass of cyclohexanone dropwise, gradually cool down, and finally stir at about 60°C for 2h to obtain a halogen-free flame retardant o-cresol type high molecular weight epoxy resin solution for copper clad laminates with a solid mass percentage of 60±2%, the viscosity of which is 1400mpas, and it is a yellow-brown liquid.

[0034] It can be seen from Examples 1-1 to 1-8 and Examples 3-7 that a halogen-free flame retardant o-cresol-formaldehyde type high molecular weight epoxy resin solution is generated under the catalytic action of o-cresol-formaldehyde epoxy resin, DOPO, bisphenol F, ethyl triphenylphosphine acetate and tetraethylammonium chloride, providing a halogen-free flame retardant o-cresol-formaldehyde modified epoxy resin with high heat resistance, high toughness, low water absorption and low glue flow loss rate for copper clad laminates with excellent comprehensive performance.

[0035] Example 8: A halogen-free flame-retardant o-cresol-formaldehyde high molecular weight epoxy resin solution composition for copper-clad laminates, comprising 90 parts by mass of a halogen-free flame-retardant o-cresol-formaldehyde high molecular weight epoxy resin solution for copper-clad laminates having a solid content of 60±2%, 12 parts by mass of a linear phenolic resin, 10 parts by mass of an ODA-type benzoxazine resin, 0.2 parts by mass of 2-ethyl-4-methylimidazole and 10 parts by mass of butanone. The above components are mixed and stirred to obtain a resin composition, which is then cured with a 7628 glass fiber cloth pressing plate. The composition has a Tg of 168°C, an impact strength (without glass fiber cloth): 45 KJ / m2, a water absorption rate of 0.28%, a pressing plate glue flow loss rate of 0.35%, and the copper-clad laminate has good toughness and does not crack or powder when drilled; and flame retardancy: UL94-V0.

[0036] Example 9: A halogen-free flame-retardant o-cresol-formaldehyde high molecular weight epoxy resin solution composition for copper-clad laminates, comprising 110 parts by mass of a halogen-free flame-retardant o-cresol-formaldehyde high molecular weight epoxy resin solution for copper-clad laminates having a solid content of 60±2%, 15 parts by mass of a linear phenolic resin, 12 parts by mass of an ODA-type benzoxazine resin, 0.7 parts by mass of 2-ethyl-4-methylimidazole and 20 parts by mass of butanone. The above components are mixed and stirred to obtain a resin composition, which is then cured with a 7628 glass fiber cloth pressing plate. The composition has a Tg of 172°C, an impact strength (without glass fiber cloth): 48 KJ / m2, a water absorption rate of 0.22%, a pressing plate glue flow loss rate of 0.31%, and the copper-clad laminate has good toughness and does not crack or shed powder when drilled; and flame retardancy: UL94-V0.

[0037] Example 10: A halogen-free flame-retardant o-cresol-formaldehyde high molecular weight epoxy resin solution composition for copper-clad laminates, comprising 100 parts by mass of a halogen-free flame-retardant o-cresol-formaldehyde high molecular weight epoxy resin solution for copper-clad laminates having a solid content of 60±2%, 13 parts by mass of a linear phenolic resin, 11 parts by mass of an ODA-type benzoxazine resin, 0.6 parts by mass of 2-ethyl-4-methylimidazole and 15 parts by mass of butanone. The above components are mixed and stirred to obtain a resin composition, which is then cured with a 7628 glass fiber cloth pressing plate. The results are as follows: Tg: 163°C; impact strength (without glass fiber cloth): 51 KJ / m2; water absorption: 0.20%; pressing plate glue flow loss rate: 0.29%. The copper-clad laminate has good toughness and does not crack or shed powder when drilled; flame retardancy: UL94-V0.

[0038] Example 11: A halogen-free flame-retardant o-cresol-formaldehyde high molecular weight epoxy resin solution composition for copper-clad laminates, comprising 95 parts by mass of a halogen-free flame-retardant o-cresol-formaldehyde high molecular weight epoxy resin solution for copper-clad laminates having a solid content of 60±2%, 12 parts by mass of a linear phenolic resin, 11 parts by mass of an ODA-type benzoxazine resin, 0.5 parts by mass of 2-ethyl-4-methylimidazole and 13 parts by mass of butanone. The above components are mixed and stirred to obtain a resin composition, which is then cured with a 7628 glass fiber cloth pressing plate. The composition has a Tg of 166°C, an impact strength (without glass fiber cloth): 42 KJ / m2, a water absorption rate of 0.26%, a pressing plate glue flow loss rate of 0.36%, and the copper-clad laminate has good toughness and does not crack or powder when drilled; and flame retardancy: UL94-V0.

[0039] Example 12: A halogen-free flame-retardant o-cresol-formaldehyde high molecular weight epoxy resin solution composition for copper-clad laminates, comprising 106 parts by mass of a halogen-free flame-retardant o-cresol-formaldehyde high molecular weight epoxy resin solution for copper-clad laminates having a solid content of 60±2%, 14 parts by mass of linear phenolic acid, 12 parts by mass of ODA-type benzoxazine resin, 0.9 parts by mass of 2-ethyl-4-methylimidazole and 18 parts by mass of butanone. The above components are mixed and stirred to obtain a resin composition, which is then cured with a 7628 glass fiber cloth pressing plate. The composition has a Tg of 170°C, an impact strength (without glass fiber cloth): 53 KJ / m2, a water absorption rate of 0.21%, a pressing plate glue flow loss rate of 0.30%, and the copper-clad laminate has good toughness and does not crack or powder when drilled; and a flame retardancy of UL94-V0.

[0040] It can be seen from Examples 2-1 to 2-8 and Examples 8-12 that a composition of resin for copper clad laminates is prepared by using a halogen-free flame-retardant o-cresol-formaldehyde high molecular weight epoxy resin solution for copper clad laminates, a linear phenolic resin, an ODA-type benzoxazine resin, 2-ethyl-4-methylimidazole and a solvent butanone. The prepared copper clad laminates have a Tg ≥ 160°C, an impact strength ≥ 40KJ / m2, a water absorption rate < 0.3%, a low glue flow loss rate of the press plate < 0.4%, and the copper clad laminates have good toughness when drilled, do not crack or shed powder, and the flame retardancy meets UL94-V0, meeting the performance requirements of the resin for copper clad laminates.

[0041] The solid amount mentioned in the present invention is defined as follows: the mass percentage of non-volatile matter in the total mass of 1g sample after baking in an oven at 160°C for 1 hour, and the solid amount finally determined by adding cyclohexanone is calculated based on the mass of non-volatile matter; That is, the definition of a halogen-free flame-retardant o-cresol-formaldehyde high molecular weight epoxy resin solution for copper-clad laminates with a solid content of 60±2% is: after 1g of the sample is baked in an oven at 160°C for 1 hour, the mass percentage of non-volatile matter in the total mass is 60±2%.

[0042] In the above embodiments: the percentages used, unless otherwise specified, are all mass (weight) percentages or percentages known to those skilled in the art; the proportions used, unless otherwise specified, are all mass (weight) proportions; and the weights may be in grams or kilograms.

[0043] In the above embodiments, the process parameters (temperature, time, etc.) in each step and the numerical values ​​of the amounts of each component are ranges, and any point can be applied.

[0044] The technical contents not specifically described in the present invention and the above embodiments are the same as the prior art, and the raw materials are all commercially available products.

[0045] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. Halogen-free flame-retardant o-cresol-formaldehyde high molecular weight epoxy resin solution for copper-clad laminates, characterized by: The halogen-free flame-retardant o-cresol-formaldehyde type high molecular weight epoxy resin solution is prepared by catalytic reaction of o-cresol-formaldehyde epoxy resin, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, bisphenol F, ethyl triphenylphosphine acetate, and tetraethylammonium chloride, and then diluted with cyclohexanone. The halogen-free flame-retardant o-cresol-formaldehyde type high molecular weight epoxy resin has the following chemical structure formula: 。 2. The halogen-free flame-retardant o-cresol-formaldehyde type high molecular weight epoxy resin solution for copper-clad laminates according to claim 1, characterized in that: The mass percentage of solid content in the halogen-free flame-retardant o-cresol-formaldehyde high molecular weight epoxy resin solution is 60±2%, the viscosity is 1000-2000 mpas, and the number average molecular weight is 3000-5000.

3. The halogen-free flame-retardant o-cresol-formaldehyde type high molecular weight epoxy resin solution for copper-clad laminate according to claim 1, characterized in that: The o-cresol epoxy resin has a chemical structural formula as shown below: , where n=3-7.

4. A method for preparing the halogen-free flame-retardant o-cresol-formaldehyde type high molecular weight epoxy resin solution for copper-clad laminates according to claim 1, characterized in that: The following steps are involved: S1: Add 30 parts by mass of cyclohexanone into a reaction kettle, start stirring, raise the temperature to 130° C., and slowly add 90 to 110 parts by mass of o-cresol epoxy resin to make it dissolve evenly; S2: Add 20-30 parts by weight of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide flame retardant monomer to the reactor, and then add 0.1-0.5 parts by weight of ethyl triphenylphosphine acetate, stir, slowly heat up to 130° C., accelerate the exothermic reaction, use cooling water to cool, control the temperature at 160-170° C., and react for 3-5 hours; S3: Then, 10 to 15 parts by weight of bisphenol F and 0.01 to 0.05 parts by weight of tetraethylammonium chloride are added to the reaction kettle, and the temperature is controlled to 170 to 180° C. to react for 4 to 6 hours; S4: After the reaction is completed, 50 to 75 parts by weight of cyclohexanone is slowly added dropwise, the temperature is gradually lowered, and finally stirred at 60° C. for 2 hours to obtain a halogen-free flame-retardant o-cresol-formaldehyde high molecular weight epoxy resin solution for copper-clad laminates having a solid mass percentage of 60±2%.

5. A halogen-free flame-retardant o-cresol-formaldehyde type high molecular weight epoxy resin solution composition for copper-clad laminates, characterized in that: The invention comprises the following components: 90 to 110 parts by weight of a halogen-free flame-retardant o-cresol-formaldehyde high molecular weight epoxy resin solution for copper-clad laminates with a solid content of 60±2%, 10 to 15 parts by weight of a linear phenolic resin, 10 to 12 parts by weight of an ODA-type benzoxazine resin, 0.2 to 1 parts by weight of 2-ethyl-4-methylimidazole and 10 to 20 parts by weight of butanone.

6. The halogen-free flame-retardant o-cresol-formaldehyde type high molecular weight epoxy resin solution composition for copper-clad laminates according to claim 5, characterized in that: The structural formula of the linear phenolic resin is: , where n=10-15.

7. The halogen-free flame-retardant o-cresol-formaldehyde type high molecular weight epoxy resin solution composition for copper-clad laminates according to claim 5, characterized in that: The structural formula of the ODA-type benzoxazine resin is: 。 8. The halogen-free flame-retardant o-cresol-formaldehyde type high molecular weight epoxy resin solution composition for copper-clad laminates according to claim 5, characterized in that: The structural formula of the 2-ethyl-4-methylimidazole is: 。

Citation Information

Patent Citations

  • Method for preparing phosphor modified flame retardation stiffening agent

    CN101928372A

  • Halogen-free epoxy resin composition for copper-clad plate and application thereof

    CN103214794A

  • Low-hydroxyl phosphorus-containing epoxy resin, composition for copper-clad plate and preparation method thereof

    CN109438673A

  • Phosphorus-containing phenoxy resin, resin composition thereof, material for circuit substrate and cured product thereof

    CN110194843A

  • Phosphorus-containing phenolic compound, phosphorus-containing epoxy resin, curable resin composition thereof, or epoxy resin composition and cured product thereof

    CN110520433A